2009
DOI: 10.1177/112067210901900413
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Biomicroscopy in Nonperforating Filtering Surgery with Intraoperative 5-fluorouracil and no implant: Long-term Results

Abstract: UBM showed a filtering intrascleral cavity, subconjunctival filtering bleb, and a suprachoroidal space after NPFS supplemented with 5-FU under the conjunctiva and the scleral flap without an implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…4 However, Cheng et al 5 showed that there were no significant differences in complete success rates among the different techniques for NDPS surgery. According to our preliminary study using UBM after the same NPDS technique, 11 we found an intrascleral space in all the patients after B5 years of follow-up and the surgical outcomes could be associated with the AS-OCT parameters of the intrascleral space. In contrast, Khairy et al, 12 in a UBM study that did not use implants or antiproliferative agents after NPDS, have reported the presence of an intrascleral space and a filtering bleb in 90.9% of the patients with an associated poor long-term IOP control after a mean followup of 28 months.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…4 However, Cheng et al 5 showed that there were no significant differences in complete success rates among the different techniques for NDPS surgery. According to our preliminary study using UBM after the same NPDS technique, 11 we found an intrascleral space in all the patients after B5 years of follow-up and the surgical outcomes could be associated with the AS-OCT parameters of the intrascleral space. In contrast, Khairy et al, 12 in a UBM study that did not use implants or antiproliferative agents after NPDS, have reported the presence of an intrascleral space and a filtering bleb in 90.9% of the patients with an associated poor long-term IOP control after a mean followup of 28 months.…”
Section: Discussionmentioning
confidence: 90%
“…[6][7][8][9][10][11][12] AS-OCT offers a good alternative to UBM for intrascleral space assessment because it uses a noncontact approach and provides higher axial resolution images of anterior segment structures (18 mm in AS-OCT vs. 25 mm in UBM) and a faster sampling rate (2.0 vs. 0.8 kHz). 13 In trabeculectomized eyes, Leung et al 14 found that the scan reveals intrableb morphology and structures, including bleb wall thickness, subconjunctival fluid collections, suprascleral fluid space, scleral flap thickness, and intrableb intensity.…”
mentioning
confidence: 99%
“…A study by Romero et al in POAG patients undergoing DS showed a correlation between IOP decline and IL height in AS-OCT. [ 17 ] Buenaga et al found a moderate inverse correlation between IL height in AS-OCT and IOP measurements after DS with Esnoper and Aquaflow implants. [ 18 ] Furthermore, other studies showed an inverse relationship between IL height in AS-OCT and IOP after DS with intraoperative 5-fluorouracil [ 27 ] or with collagen implants [ 15 ] . Furthermore, Konstantopoulos et al claimed that the height of the bleb or IL correlates with the success rate of filtering procedures.…”
Section: Discussionmentioning
confidence: 99%
“…En effet, Aptel et al, ont démontré en 2009 qu'une PIO basse était corrélée avec la hauteur de la bulle, une petite épaisseur restante de membrane trabéculocornéenne et du mur de la bulle, ainsi que la présence de beaucoup de fluide dans l'espace sous-conjonctival et une bulle hyporéflective (10). Alors que Gutiérrez-Ortiz et al ont publié, quelques mois plus tard, les résultats d'une étude qui démontrait qu'il n'y a pas de corrélation entre la hauteur, la largeur, le volume du lac sous-scléral et la PIO (11). Notre étude a essentiellement pour but de mettre en évidence le pourcentage de bulles fonctionnelles après une longue période.…”
Section: Discussionunclassified